2005
DOI: 10.1016/j.febslet.2005.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Interchange of aequorin and obelin bioluminescence color is determined by substitution of one active site residue of each photoprotein

Abstract: The bioluminescence spectra from the Ca 2+ -regulated photoproteins aequorin (k max = 469 nm) and obelin (k max = 482 nm) differ because aequorin has an H-bond from its Tyr82 to the bound coelenteramide, not present in obelin at the corresponding Phe88. Substitutions of this Phe88 by Tyr, Trp, or His shifted the obelin bioluminescence to shorter wavelength with F88Y having k max = 453 nm. Removal of the H-bond by the substitution of Y82F in aequorin shifted its bioluminescence to k max = 501 nm. All mutants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 48 publications
(62 reference statements)
4
85
0
Order By: Relevance
“…We found that the kinetics and sensitivity to Mg 21 of GFP-photoprotein fusions were similar to those of their cognate photoproteins. Indeed, values of these parameters for GA and GO responses were in the range of those reported for native (Hastings et al, 1969;Morin and Hastings, 1971a;Stephenson and Sutherland, 1981) and recombinant (Illarionov et al, 2000;Markova et al, 2002;Stepanyuk et al, 2005) aequorin and obelin. In the present study, we also found that kinetics and Mg 21 sensitivity of GA and GA N26D responses were similar to those of aequorin and aequorin N26D , respectively.…”
Section: Kinetic Properties Of Gfp-photoprotein Responses In Vitromentioning
confidence: 67%
See 1 more Smart Citation
“…We found that the kinetics and sensitivity to Mg 21 of GFP-photoprotein fusions were similar to those of their cognate photoproteins. Indeed, values of these parameters for GA and GO responses were in the range of those reported for native (Hastings et al, 1969;Morin and Hastings, 1971a;Stephenson and Sutherland, 1981) and recombinant (Illarionov et al, 2000;Markova et al, 2002;Stepanyuk et al, 2005) aequorin and obelin. In the present study, we also found that kinetics and Mg 21 sensitivity of GA and GA N26D responses were similar to those of aequorin and aequorin N26D , respectively.…”
Section: Kinetic Properties Of Gfp-photoprotein Responses In Vitromentioning
confidence: 67%
“…Hence, our results show that kinetics of GFP-photoprotein fusions GA, GO, and GA N26D are markedly different, as expected from data obtained on photoproteins alone in previous studies. Indeed, onset and decay time constants of 10 msec and 833 msec, respectively, were obtained for aequorin (Hastings et al, 1969), whereas these values were 2.5-4 msec and 139-294 msec, respectively, for obelin depending on the Obelia species (Morin and Hastings, 1971a;Stephenson and Sutherland, 1981;Illarionov et al, 2000;Stepanyuk et al, 2005). Similarly, the aequorin N26D mutant reportedly exhibits slower decay kinetics than wild-type aequorin (Tricoire et al, 2006).…”
Section: Kinetics Of Calcium Sensor Responses In Vitromentioning
confidence: 83%
“…Although there are differences in spectral properties among them, it has been already demonstrated that these are due to different interactions of the coelenteramide with the side chains of residues making up the binding cavity (32,36). Kinetic properties, Ca 2ϩ sensitivity, thermostability, and so on, are much more difficult to account for, in common with trying to account for enzymatic properties from structural information in general.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the Ca 2þ -discharged obelins show fluorescence maxima about 25 nm to longer wavelength than their bioluminescence. Furthermore, the obelin bioluminescence spectrum is bimodal, with a minor higher energy band having a maximum around 400 nm, not evident in aequorin bioluminescence (9,10). From spectral studies of model compounds, this high energy band is identified as from the excited level of coelenteramide in its neutral state (11).…”
mentioning
confidence: 99%